2021
DOI: 10.1088/1752-7163/ac3096
|View full text |Cite
|
Sign up to set email alerts
|

IABR Symposium 2021 meeting report: breath standardization, sampling, and testing in a time of COVID-19

Abstract: Due to COVID-19 travel disruptions, the International Association of Breath Research hosted the planned 2021 Breath Summit virtually as a symposium with oral and poster presentations. The event was comprised of a week-long social media asynchronous online event for sharing research abstracts, posters and discussions. Subsequently, there were two days of real-time webinar platform interactions each featuring three technical presentations, open forum questions, answers, and commentary. The symposium was well att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Carvone, a trace level component of peppermint oil capsule was suppressed by both filters and was only detected in 3 out of 18 filtered samples, where in non-filtered samples the compound was found in 6 out of 9 cases. Similar effect of use of filters on detection of peppermint oil components in breath was observed and described in another study [18]. Similarly, ethanol, benzaldehyde and 3methyl thiophene (commonly reported breath biomarkers) were also suppressed when using the Spiro filter and benzene_1_2_4_5_tetramethyl when using syringe filter.…”
Section: Filter Resultssupporting
confidence: 82%
“…Carvone, a trace level component of peppermint oil capsule was suppressed by both filters and was only detected in 3 out of 18 filtered samples, where in non-filtered samples the compound was found in 6 out of 9 cases. Similar effect of use of filters on detection of peppermint oil components in breath was observed and described in another study [18]. Similarly, ethanol, benzaldehyde and 3methyl thiophene (commonly reported breath biomarkers) were also suppressed when using the Spiro filter and benzene_1_2_4_5_tetramethyl when using syringe filter.…”
Section: Filter Resultssupporting
confidence: 82%
“…Clinical practices have been developed to safely collect, handle, and deactivate potentially transmissible viral material in breath vapor samples for COVID-19 screening [11][12][13] . Worldwide, breath research groups have shown that exhaled vapor reflects SARS-CoV-2 infection status [14][15][16] .…”
mentioning
confidence: 99%
“…We have witnessed the ubiquitous hurdles faced by the scientists and/or clinicians while dealing with SARS-CoV-2 infected subjects 17 , 18 . Mandatory safety and precaution measures have often overruled/compromised sampling and analytical requirements/standards, which have affected the quality, reliability and reproducibility of obtained data 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%